BALANCED SCORECARD SEBAGAI METODE MENINGKATKAN KELANGSUNGAN USAHA SUPERMARKET PADA MASA PANDEMI COVID-19 - Anindya, Anindya; Novita, Novita (Universitas Trilogi, 2023)
The purpose of this research is to find out that a performance measurement system with a balanced scorecard can be a tool for maintaining the continuity of Papaya Fresh Gallery's business so that it can survive during the pandemic. This research uses the method of analysis of validity test, reliability test, descriptive qualitative, and also descriptive quantitative. Primary data is obtained through questionnaires distributed to customers and employees, while secondary data is obtained from financial reports, that are appropriate to the topic as well as from journals. The results obtained from this study show that with COVID-19 which caused a global crisis, performance measurement with the balanced scorecard is useful for decision-making in making performance designs so that companies can know the compcompanyition to be able to make decisions and make strategies to survive and compete. with other foreign supermarkets as well as with other competitors so that the company can continue its business.Keywords: Balanced Scorecard, Business Continuity, Performance measurement